Flocculation of Riverine Sediment Draining to the Great Barrier Reef, Implications for Monitoring and Modeling of Sediment Dispersal Across Continental Shelves. Issue 7 (20th July 2022) - Livsey, D. N.; Crosswell, J. R.; Turner, R. D. R.; Steven, A. D. L.; Grace, P. R.
Abstract: Sediment transport models, utilized to guide land management in the Great Barrier Reef (GBR), assume settling velocities for individual silt and clay particles on the order of 0.01 mm/s; however, silts and clays once flocculated exhibit settling velocities on the order of 1 mm/s. In this study, in‐situ ( n = 144, 912) and laboratory‐dispersed ( n = 64) particle size measurements collected using laser diffractometry were compared from nine rivers discharging along 800 km of GBR coastline to determine the extent of in‐situ flocculation. Environmental controls on in‐situ particle size were investigated using decision tree algorithms trained on coeval measurements of salinity, shear rate, and turbidity. Comparison of in‐situ and dispersed particle size measurements demonstrate that suspended‐sediment across all catchments flocculated into larger aggregates with an order‐of‐magnitude difference in median particle size between in‐situ ( D 50v = 132 μm, σ = 60 μm for all data) and dispersed ( D 50v = 15 μm, σ = 11 μm for all data) particles. Machine learning algorithms showed excellent promise predicting various measures of in‐situ particle size. Model validation R 2 ranged from 0.72 to 0.99, inclusion of catchment as a categorical variable only marginally (<1%) increased R 2 . These results demonstrate that flocculation is prevalent across all rivers surveyed and that hydrodynamics are more important than inter‐catchment differences (e.g., differences in climate, geology, or land‐use). Implications of widespread flocculation on the determination of end‐of‐catchment sediments loads and subsequent dispersal patterns across continental shelves are discussed to inform the refinement and monitoring of GBR sediment targets. Plain Language Summary: Dispersal of fine riverine sediment, namely silt and clay, throughout the Great Barrier Reef (GBR) impacts water clarity and resiliency of the reef to ongoing changes in climate. Currently, sediment transport models, utilized to track progress toward water quality targets, assume fine sediment is transported as individual, 1–10 μm, slow‐settling (0.01–0.1 mm/s) particles. However, studies globally indicate that fine riverine sediment is often transported as faster‐settling (1–10 mm/s), larger (100–1, 000 μm) aggregates or "flocs". Because the settling velocity of suspended sediment, along with prevailing currents, controls sediment dispersal distance, current models may incorrectly estimate sediment dispersal if suspended sediment is flocculated. In this study, the particle size of suspended sediment present in the estuarine sections of nine rivers encompassing 800 km of coastline adjacent to the GBR were measured. Both in‐situ and dispersed particle size of suspended sediment were investigated to quantify the extent of flocculation. Comparison of in‐situ and dispersed measurements demonstrate that suspended‐sediment across all catchments flocculated into larger aggregates with an order‐of‐magnitude difference in size between in‐situ (132 μm) and dispersed (15 μm) particles. Implications of widespread flocculation are discussed to inform the refinement and monitoring of sediment targets in the GBR. Key Points: Fine riverine sediment draining to the Great Barrier Reef is flocculated with settling velocity on the order of 1 mm/s Sediment transport models utilized to guide land management assume settling velocity for individual particles on the order of 0.01 mm/s Implications of widespread flocculation are discussed to inform monitoring and modeling of sediment dispersal across continental shelves